Integrated use of polyphosphate and P-solubilizing bacteria enhanced P use efficiency and growth performance of durum wheat - Khourchi, Said; Elhaissoufi, Wissal; Ibnyasser, Ammar; Haddine, Meryem; Ghani, Rachid; Zeroual, Youssef; Delaplace, Pierre; Bargaz, Adnane (Frontiers in Microbiology, 2023)
Coupling phosphate-solubilizing bacteria (PSB) with P fertilizers, including polyphosphates (PolyP), was reported as eco-efficient approach to enhance P use efficiency. Although PSB have been recently reported to hydrolyze PolyP, the plant growth promoting mechanisms of PolyP-PSB co-application were not yet uncovered. This study aims to evaluate the effect of a PSB consortium (PSBCs) on growth, P use efficiency (PUE), and wheat yield parameters under PolyP (PolyB) application. Co-application of PolyB-PSBCs significantly enhanced wheat growth at 75 days after sowing (DAS) compared to 30 DAS. A significant increase in shoot dry biomass (47%), shoot inorganic P content (222%), PUE (91%), and root P absorption efficiency (RPAE, 99%) was noted compared to unfertilized plants. Similarly, the PolyB-PSBCs co-application enhanced morphological root traits at 30 DAS, while acid phosphatase activities (root and rhizosphere), RPAE, and PUE were significantly increased at 75 DAS. The improved wheat P acquisition could be attributed to a lower investment in root biomass production, and significant induction of acid phosphatase activity in roots and rhizosphere soil under PolyB-PSBCs co-application. Consequently, the PolyB-PSBCs co-application significantly improved aboveground performance, which is reflected by increased shoot nutrient contents (P 300%, K 65%), dry weight (54%), and number (50%) of spikes. Altogether, this study provides relevant evidence that co-application of PolyP-PSBCs can be an integrated and environmentally preferred P fertilization approach owing to the dual effects of PolyP and PSBCs on wheat PUE.